1998
DOI: 10.1159/000027623
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuropathy Caused by an Isolated Mucocele in an Onodi Cell

Abstract: A rare case of retrobulbar optic neuropathy caused by an isolated mucocele in an Onodi cell is presented. A 63-year-old man suffering from left recurrent optic neuropathy had shown improved visual acuity with steroid treatment at the age of 48 and 56 years. Impaired visual acuity and blurred vision in the left eye appeared again, and a marked inferior decrease in the left visual field was noted. Although axial computed tomography (CT) showed no abnormal findings, magnetic resonance imaging (MRI) revealed a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Neuroimaging is central to the detection of the lesion, and coronal and sagittal views are recommended, as axial CT images alone may not reveal the mucocele if the thickness of the slices used is greater than the width of the Onodi cell [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging is central to the detection of the lesion, and coronal and sagittal views are recommended, as axial CT images alone may not reveal the mucocele if the thickness of the slices used is greater than the width of the Onodi cell [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Optic neuropathy is a well known complication of paranasal sinusitis and mucoceles,7 but there are only few cases in literature which describe an isolated mucocele in an Onodi cell as the cause of optic neuropathy 89 The mechanism of retrobulbar optic neuropathy is a mechanical compression of the optic nerve, because it often runs within the small cavity of the Onodi cell 6…”
Section: Commentmentioning
confidence: 99%
“…9 Coronal computed tomography is helpful in the differential diagnosis of an osseous origin and preoperative evaluation 23 8 9 …”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Onodi cells have been reported to occur in approximately 7% of the general population in computed tomography (CT) studies, but in cadaveric studies they have been reported to be present in up to 60% of specimens [3]. The discrepancy may be due in part to the fact that older studies using thick section axial CT without isotropic resolution were less sensitive for detecting small air cells which are often flat in configuration within the plane of axial section [4]. Identification of an Onodi cell is of importance prior to sinonasal surgery due to the close anatomic relationship between this posterior air cell and the optic nerve ( [5]; Fig.…”
Section: Introductionmentioning
confidence: 99%